The Effect of Family-based Intervention on Overweight/ Obesity in Children: Meta Analysis - Sani, Mario Febrianus Helan; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Childhood overweight and obesity is one of the most serious public health challenges of the 21st century. Overweight and obesity are one side of the double burden of malnutrition because more than 1.9 billion people are overweight and of that number more than 650 million are obese. Meanwhile, for children aged 5-19 years, more than 340 million children are overweight and obese. One category of intervention to prevent overweight / obesity in children who have developed rapidly in recent years is family-based intervention. This study aims to estimate the magnitude of the effect of family-based intervention on overweight / obesity based on the results of a number of previous studies.Subjects and Method: This was a systematic study and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles through a journal database which includes: Google Scholar, PubMed, ScienceDirect and SpingerLink by selecting articles published in 2005-2020. Keywords used include: “family-based intervention” OR “family-based program” OR “family-based treatment” OR “family-based” OR “home-based intervention” OR “household based intervention” AND “children overweight OR